Peran Iman dalam Mengatasi Stres dari Tinjauan Perspektif Psikologi Islam: Lierature Review: The Role of Faith in Managing Stress from the Perspective of Islamic Psychology: A Literature Review - Siti Fatimah; Salsabila Nasution (Litera Academica Publishing, 2025)
Stress is a psychological challenge that affects an individual's mental health, making effective management strategies necessary. This research aims to examine the role of faith and religious practices in managing stress. The research method used is a literature review with a descriptive qualitative approach. Data were collected from national journals, scientific articles, and relevant Islamic literature, with sources selected based on recency and relevance. The results indicate that faith and religious practices such as prayer (salat), supplication, remembrance (dhikr), patience, and sincerity play a role in cultivating inner peace, strengthening psychological resilience, and helping individuals face life's pressures more adaptively. These findings affirm that Islamic psychology offers a comprehensive stress management strategy, covering cognitive, emotional, and spiritual aspects, making it relevant for application in supporting the mental health of students and society at large.